PERAN GURU AGAMA KATOLIK DALAM MENINGKATKAN MOTIVASI BELAJAR AGAMA KATOLIK PESERTA DIDIK DI PAROKI ST. MIKAEL TAMIANG LAYANG - Milayani Milayani; Paulina Maria E.W.; Timotius Tote Jelahu; Greget Widhiati (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2019)
This study aims to find out and understand the extent of the role of Catholic religious teachers in providing motivation in order to help students to improve their learning motivation about Catholic religious education so that students will increasingly understand the faith they believe in in the future. The method used in this study is a qualitative research method. Data collection techniques in this study use observation, interviews and documentation. The speakers used in this study were 3 Catholic religious teachers and 8 students. The data analysis technique of this study uses the Miles and Huberman analysis technique which is divided into three stages, namely Data Reduction, Data Disply and Conclusion / verification.